Istihsan Methodology In The Productive Waqf Application - Sudirman Suparmin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
Istihsan is a form of ijtihad method by calculating the law of a problem so that it is better for certain reasons as long as it does not violate Islamic law. Istihsan based on the argument used is divided into three: first, switching from qiyas dzahir to qiyas khafi; second, switching from general propositions to specific characteristics; third from Kulli's law to exceptions to legal exclusion (exceptions). Meanwhile, based on the backrest taken by mujtahid divided into four types; istihsan qiyasi, istihsan nashi, istihsan bi al-’urf and istihsan dharuri. Earning cash in the form of cash is a new phenomenon that is still often debated about its legality as a solution of the Islamic religion. This paper explains the role of istihsan methodology in restoring contemporary economic activities in the form of productive endowments. Based on its practices and functions, cash waqf has enormous benefits for the economic progress of the community. With the analysis of the istihsan methodology, it can be seen that the cash waqf law is permissible to review using the istihsan bi al-’urf approach